It’s Not All Objectivity and Development: Documentation Dilemmas and Discoveries in a Toddler Classroom - Fincham, Emmanuelle N. (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
This article seeks to explore a process of ongoing engagement with classroom documentation, returning to pieces of data and drawing on teaching experiences from a toddler classroom. In response to pervasive narratives in early childhood education that link practices of observation and documentation with accountability and assessment, a self-reflexive inquiry into the discursive forces that guide teachers’ representations of children is taken up. Drawing at times on feminist poststructural theories and new materialisms, imaginings for more expansive possibilities for reconceptualizing documentation are discussed.